The Us Approach To The October 7 Attacks And The Israel-Hamas Conflict In The Context Of Antony Blinken's Discourses - Orhan, Ertuğrul Buğra (My University, 2024)
The risk of the political friction between Israel and Hamas escalating into an armed conflict has been a source of great concern worldwide. Aligning with this pessimistic anticipation, on October 7, 2023, Hamas initiated a military action from Gaza into Israel, prompting Israel to respond with a significantly devastating counteroffensive. The military operation specifically targeted places populated by civilians and elicited a response from the global community. US Secretary of State Antony Blinken engaged in numerous meetings and conducted a series of press interviews during this time. These interviews were subsequently published in text format on the official website of the US State Department. The objective of this study is to examine the discourse content of Antony Blinken's interviews regarding the Israel-Hamas conflict. The discourse content was thoroughly examined using discourse analysis. The conversation materials were analyzed using Rstudio, a code-based application. The analysis demonstrates that Blinken disregards the human rights violations committed during Israeli acts of aggression. However, Hamas was held responsible for these transgressions. Iran and Hamas were linked to terrorism as a result of their affiliation. Blinken consistently places a high importance on Israel's security in his language and communication. Blinken's affirmation of his Jewish identity during his initial visit to Israel following recent events confirmed the theopolitical connection between the US and Israel. Furthermore, it was noted that Blinken's words endorsed the framework of the religious ties between the United States and Israel. It was noted that Blinken's use of language focusing on the civilian population in Gaza did not have an impact on the current situation on the ground. The US's lack of success in providing humanitarian relief can also be attributed to its unwavering support for Israel, as reflected in Blinken's rhetoric.
Keywords: US; Israel; Hamas; Conflict; Discourse Analysis; Gaza; Antony Blinken